Lean-non-alcoholic fatty liver disease increases risk for metabolic disorders in a normal weight Chinese population - Feng, Ren-Nan; Du, Shan-Shan; Wang, Cheng; Li, Yan-Chuan; Liu, Li-Yan; Guo, Fu-Chuan; Sun, Chang-Hao (World journal of gastroenterology : WJG, 2014)
AIM:To study the prevalence and clinical biochemical,blood cell and metabolic features of lean-non-alcoholic fatty liver disease(lean-NAFLD)and its association with other diseases.METHODS:Demographic,biochemical and blood examinations were conducted in all the subjects in this study.We classified the subjects into four groups according to their weight and NAFLD status:lean-control,lean-NAFLD[body mass index(BMI)<24 kg/m2],overweight-obese control and overweight-obese NAFLD.One-way analysis of variance(ANOVA)was used to compare the means of continuous variables(age,BMI,blood pressure,glucose,lipid,insulin,liver enzymes and blood cell counts)and theχ2 test was used to compare the differences in frequency of categorical variables(sex,education,physical activity,smoking,alcohol consumption and prevalence of hypertension,hyperlipidemia,diabetes,metabolic syndrome central obesity and obesity).Both univariate and multivariate logistic regression models were adopted to calculate odds ratios(ORs)and predict hyperlipidemia,hypertension,diabetes and metabolic syndrome when we respectively set all controls,lean-control and overweightobese-control as references.In multivariate logistic regression models,we adjusted potential confounding factors,including age,sex,smoking,alcohol consumption and physical activity.RESULTS:The prevalence of NAFLD was very high in China.NAFLD patients were older,had a higher BMI,waist circumference,blood pressure,fasting blood glucose,insulin,blood lipid,liver enzymes and uric acid than the controls.Although lean-NAFLD patients had lower BMI and waist circumstance,they had significantly higher visceral adiposity index than overweightobese controls.Lean-NAFLD patients had comparable triglyceride,cholesterin and low-density lipoprotein cholesterin to overweight-obese NAFLD patients.In blood cell examination,both lean and overweightobese NAFLD was companied by higher white blood cell count,red blood cell count,hemoglobin and hematocrit value.All NAFLD patients were at risk of hyperlipidemia,hypertension,diabetes and metabolic syndrome(Met S).Lean-NAFLD was more strongly associated with diabetes(OR=2.47,95%CI:1.14-5.35),hypertension(OR=1.72,95%CI:1.00-2.96)and Met S(OR=3.19,95%CI:1.17-4.05)than overweight-obese-NAFLD(only OR for Met S was meaningful:OR=1.89,95%CI:1.29-2.77).NAFLD patients were more likely to have central obesity(OR=1.97,95%CI:1.38-2.80),especially in lean groups(OR=2.17,95%CI:1.17-4.05).CONCLUSION:Lean-NAFLD has unique results in demographic,biochemical and blood examinations,and adds significant risk for diabetes,hypertension and Met S in lean individuals.